Pregnancy Outcomes in Women with Gestational Diabetes Mellitus Diagnosed in the First Versus Second Trimester [31E]. (May 2018) - Fahey, Jacqueline; Wong, Thalia; Afshar, Yalda; Scibetta, Emily; Janzen, Carla; Rao, Rashmi
Abstract : INTRODUCTION: First trimester screening is recommended for patients at higher risk for gestational diabetes mellitus (GDM). We sought to compare pregnancy outcomes in women diagnosed with GDM in the first versus second trimester. METHODS: This was a retrospective cohort study evaluating patients with GDM at a university clinic. The early diagnosis group had abnormal first trimester GDM testing. The late diagnosis group had normal first trimester testing, followed by abnormal second trimester testing. Mean differences in treatment interventions and maternal/neonatal outcomes were compared between groups. RESULTS: Of 115 total patients, 32 (28%) were diagnosed with GDM in the first trimester and 83 (72%) were diagnosed in the second trimester. There was no difference in number of antenatal testing visits, ultrasounds, or patients requiring medication for glycemic control (p = 0.78, p = 0.92, p = 0.92). Mean gestational age at medication initiation was earlier in the early diagnosis group (24.2 vs. 31.5 weeks; p < 0.001). There was no clinically meaningful difference in mean number of prenatal visits (11.7 vs. 10.4; p = 0.04) or nutrition consults (2.2 vs. 1.7; p = 0.005). Both groups had similar incidence of cesarean delivery and postpartum hemorrhage (p = 0.87, p = 0.57). There was no difference in minor or major adverse neonatal composite outcomes (p = 0.74, p = 0.48). CONCLUSION: Early GDM diagnosis and intervention in high-risk patients may positively impact their pregnancy by achieving similar maternal and neonatal outcomes without increasing the burden of clinic visits compared to those diagnosed in the second trimester.